MAKNA BUAH ROH DALAM GALATIA 5:22-23 - Minggus Dilla (Manna Rafflesia, 2015)
The fruit of the Spirit is the most important part in the life of a believer. Through the Fruit of the Spirit the believer can show his true self. But the understanding of the Fruit of the Spirit is still not widely known by many Believers. Therefore through this article believers can have an understanding of what the fruit of the Spirit is and its meaning in its relation to daily life.